Penggunaan Powtakon Kardus Sebagai Upaya Meningkatkan Hasil Belajar Peserta Didik SDN 2 Kembang - Zuliyanti, Nurma (Jurnal Didaktika Pendidikan Dasar, 2021)
These classroom action research aims: To improve student learning outcomes using Powtakon kardus media. The research setting was grade V students of SDN 2 Kembang Jepara for the 2019/2020 academic year. This study consisted of 2 cycles in one basic competency. The research begins with compiling a lesson plan, making observation sheets and other research instruments. During the learning process, observations were made on the performance of the teacher as a researcher, and an assessment was made of students through test sheets. Other findings during the learning process were discussed between the researcher and the observer, equipped with data from observations made by reflection at each meeting. The results of research in cycle 1 and cycle 2 showed an increase in student learning outcomes. The student learning outcomes are in cycle 1 an average of 66.33 with learning completeness 40%, in cycle 2 an average of 81.27 with learning completeness 86.67%. Based on the results of the study, it can be concluded that the learning process using powtakon kardus media can improve student learning outcomes in Class V SDN 2 Kembang Jepara for the 2019/2020 academic year.